Donor cytomegalovirus serology impacts overall survival in children receiving first unrelated hematopoietic stem cell transplant for acute leukemia: European Society of Bone Marrow Transplantation Pediatric Diseases Working Party Study - Elif Ince; Jaques-Emmanuel Galimard; Marianne Ifversen; Arnaud Dalissier; Zofia Szmit; Oana Mirci-Danicar; Franco Locatelli; Petr Sedlacek; Jan Styczynski; Jean-Hugues Dalle; Cecile Renard; Adriana Balduzzi; et al. (Haematologica)
Not available.